OP68 Trends in cardiovascular diseases mortalities by subtypes in England and Wales from 2001 to 2019*. (26th August 2022) - Cuitun Coronado, Jose Ignacio; Fleming, Kate; Kypridemos, Chris; O'Flaherty, Martin
Abstract : Background: Cardiovascular disease (CVD) is one of the leading causes of death globally. In 2019, an estimated 17.9 million people died from CVD, representing 32% of all global deaths. In the United Kingdom (UK), around 7.6 million people live with a heart or circulatory disease, causing around 160, 000 deaths and more than 100, 000 hospital admissions each year. This project aimed to investigate the trends in sex and age-specific cardiovascular disease mortality by subtypes in England and Wales. Methods: Mortality data from 2001 to 2019 from the Office for National Statistics (ONS), coded using the International Classification of Disease, Tenth Revision (ICD-10), we focused on stroke-specific and heart disease subtypes causes of death. Analyses were limited to people aged 35 years and older, categorised as < 45 years, 45–64 years, and ≥ 65 years. Directly age-standardized mortality rates to the 2013 European Standard Population were used to identify and compare differences by age and sex over time. Analyses were generated using R v4.1.2., and the Join point software v4.9.0.0. Results are displayed as percentages (%) with 95% confidence intervals where appropriate. Results: From 2001 to 2019, deaths by ischemic stroke decreased (from 1.45% to 0.592%), alongside heart failure (from 0.373% to 0.192%), and ischemic heart disease (from 3.82% to 2.01%). A decrease in the rate of decline (%) was observed in ischemic stroke (-8.54, [-9.15, -7.92] in 2003–2011 to 4.39 [5.02, -3.76] in 2011–2019), ischemic heart disease (-6.50 [-6.93, -6.0] in 2003–2011 to -3.90 [-4.31, -3.49] in 2011–2019). Heart failure showed two decrease periods (-14.54 [-23.08, -5.06] in 2010–2014, and 2.43 [-2.37, 7.47] in 2014–2019). Although the overall trends by population showed that most diseases of the circulatory system are decreasing, the diseases that showed the highest rate of increase per year were arrhythmia (3.45%), hypertensive heart disease (1.93%), and valvular heart disease (0.91%). The highest rate of increase in mortality aged under 45-years old was seen in arrhythmia (6.63%), for people aged 65-year-old hypertensive heart disease (2.02%), and valvular heart disease (1.09%). Conclusion: Between 2001 and 2019, trends in the mortality rate for arrhythmia, hypertensive heart disease, and valvular heart disease accounted for the fastest increase in mortality for the overall population by age and sex. The recent slowdown in ischemic stroke and ischemic heart disease suggests that the overall burden of CVD mortality will likely increase if trends persist.